2013
DOI: 10.1159/000356041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Joint Detection of CD44v6 and CD62P in Nasopharyngeal Carcinoma

Abstract: Aim: The aim of this study was to investigate the expression and clinical prognostic significance of adhesion molecules in nasopharyngeal carcinoma (NPC) tissues and peripheral blood. Materials and Methods: Flow cytometry assays for the expression levels of CD44v6 and CD62P protein in peripheral blood and tissues from controls and NPC patients were performed. Clinical and pathological features were reported and analyzed, and a survival study was carried out. Results: The expression of CD44v6 and CD62P in NPC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another report showed that both CD24- and CD44-positive populations had stem-like properties under physiological Wnt/beta-catenin signaling [27]. Expression of CD44v6, a splicing variant of CD44, is associated with clinical significance by joint detection of CD62P in peripheral blood of NPC patients [28]. Several reports suggest that CD44v6 has more aggressiveness as the stem cell marker than CD44 [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Another report showed that both CD24- and CD44-positive populations had stem-like properties under physiological Wnt/beta-catenin signaling [27]. Expression of CD44v6, a splicing variant of CD44, is associated with clinical significance by joint detection of CD62P in peripheral blood of NPC patients [28]. Several reports suggest that CD44v6 has more aggressiveness as the stem cell marker than CD44 [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…These include including PAX8 (implicated in adenocarcinoma and ovarian carcinoma), SELP (nasopharyngeal carcinoma) and RAB40C (gastric cancer). [195][196][197][198] As previously discussed, we hypothesised that the biological causes for LAF varied between the histological groups making it difficult to differentiate all samples based on LAF alone. In support of this, the differential expression profile between the LAF groups within the keratosis/hyperplasia group present different underlying mechanisms to those in the dysplasia group.…”
Section: Discussionmentioning
confidence: 95%